The ulnar ratio as a sensitive and specific marker of acute inflammatory demyelinating polyneuropathy. Issue 8 (August 2018) - Ahdab, Rechdi; Noureldine, Mohammad Hassan A.; Mohammedi, Kamel; Nader, Manal; Zouari, Hela G.; Nordine, Tarik; Créange, Alain; Lefaucheur, Jean-Pascal; Ayache, Samar S.
Highlights: Ulnar ratio definition: SNAP amplitude of palmar cutaneous over that of dorsal branch of ulnar nerve. Ulnar ratio ≥ 0.78 can rule out diagnosis of Acute Inflammatory Demyelinating Polyneuropathy (AIDP), with high specificity (100%) and sensitivity (87%). Incorporating specific sensory abnormalities in AIDP criteria may enhance their reliability. Abstract: Objectives: To explore the value of a novel sensory criterion, the ulnar ratio – defined as the SNAP amplitude of the palmar cutaneous (pUN) over that of the dorsal branch (dUN) of the ulnar nerve – as a predictor of Acute Inflammatory Demyelinating Polyneuropathy (AIDP). Methods: We prospectively included 22 patients with AIDP, 20 patients with diabetic peripheral neuropathy (DPN), and 18 controls. Eligible subjects underwent nerve conduction studies including, among others, the dUN, pUN, and sural nerve. Results: A sural sparing pattern was found in 72% of AIDP cases. The ulnar ratio was significantly lower in patients with AIDP compared to those with DPN or controls. The ROC curve area to discriminate AIDP (versus controls and diabetics together) was higher with the ulnar ratio and pUN compared to dUN. An ulnar ratio ≥ 0.78 seems to be the best threshold to rule out the diagnosis of AIDP, with a specificity of 100% and a sensitivity of 87%. The ulnar ratio was equally reliable in the subgroup of patients presenting within a week of symptoms onset. Conclusion: The ulnar ratio is a highly sensitive and specific marker of AIDP and can help confirm the diagnosis when direct signs of demyelination are lacking. Significance: Incorporating specific sensory abnormalities, such as the ulnar ratio, in the electrodiagnostic criteria of AIDP could enhance their reliability.